Day after: The impact of the launch of the Russian-language television channel ETV+ on Estonian Public Broadcasting’s viewing trends (Translation into Russian) - Андрес Йыэсаар (Communications. Media. Design, 2017)
At a time when many public broadcasters are closing down channels, the Estonian Public Broadcasting (ERR) launched a new channel on September 28, 2015. The aim of this study is to see how ERR’s recently launched Russian-language television channel ETV+ changed the competitive environment. The Estonian Public Broadcasting Act (2007) established nine goals for Estonian Public Broadcasting. Two of these focus on increasing social cohesion in the society and assisting in the promotion of the democratic form of government and, as much as possible, meeting the information needs of all segments of the population, including minorities. This article uses two indicators for analysing the changes in the Estonian Public Broadcasting viewers between January 2006 and May 2017 – the weekly reach and share of general viewing time (data from TNS Emor TV-audience surveys). Using these indicators, it is possible to discern the trends that have taken place on a timeline, and predict the ability of Estonian Public Broadcasting to fulfil the goals required by law by extrapolating these trends into the future. The article focuses on the TV viewing trends of the Russian-speaking audience and assesses how effectively Estonian Public Broadcasting (TV channels) has fulfilled the goals and functions required by law related to meeting the information needs of the population, especially the Russian-speaking population.Full English version of the article is here.